AGM-consistency and perfect Bayesian equilibrium. Part II: From PBE to sequential equilibrium - Giacomo Bonanno (University of California, Department of Economics, 2014)
In Bonanno (Int. J. Game Theory, 42:567-592, 2013) a general notion of perfect Bayesian equilibrium (PBE) was introduced for extensive-form games and shown to be intermediate between subgame-perfect equilibrium and sequential equilibrium. The essential ingredient of the proposed notion is the existence of a plausibility order on the set of histories that rationalizes a given assessment. In this paper we study restrictions on the belief revision policy encoded in a plausibility order and provide necessary and sufficient conditions for a PBE to be a sequential equilibrium.
Keywords: C7; 330; plausibility order; belief revision; Bayesian updating; independence; sequential equilibrium; consistency